Real-world experience with cefiderocol therapy for Pseudomonas aeruginosa and other multidrug resistant gram-negative infections within the Veterans Health Administration, 2019-2022 - Andrew Chou; David Ramsey; Eva Amenta; Barbara W. Trautner (Cambridge University Press, 2023)
Abstract Objective: Single-center and regional studies have reported outcomes after treatment with cefiderocol, a novel siderophore cephalosporin. We report on real-world use, clinical outcomes, and microbiological outcomes with cefiderocol therapy within the Veterans' Health Administration (VHA). Design: Prospective, observational descriptive study. Setting: Veterans' Health Administration, 132 sites across the United States, during 2019-2022. Patients: This study included patients admitted to any VHA medical center who received cefiderocol for ≥2 days. Methods: Data were obtained from the VHA Corporate Data Warehouse and through manual chart review. We extracted clinical and microbiologic characteristics and outcomes. Results: In total, 8,763,652 patients received 1,142,940,842 prescriptions during the study period. Of these, 48 unique individuals received cefiderocol. The median age of this cohort was 70.5 years (IQR, 60.5-74), and the median Charlson comorbidity score was 6 (IQR, 3-9). The most common infectious syndromes were lower respiratory tract infection in 23 patients (47.9%) and urinary tract infection in 14 patients (29.2%). The most common pathogen cultured was P. aeruginosa in 30 patients (62.5%). The clinical failure rate was 35.4% (17 of 48), and 15 (88.2%) of these 17 patients died within 3 days of clinical failure. The 30-day and 90-day all-cause mortality rates were 27.1% (13 of 48) and 45.8% (22 of 48), respectively. The 30-day and 90-day microbiologic failure rates were 29.2% (14 of 48) and 41.7% (20 of 48), respectively. Conclusions: In this nationwide VHA cohort clinical and microbiologic failure occurred in >30% of patients treated with cefiderocol, and >40% of these died within 90 days. Cefiderocol is not widely used, and many of the patients who received it had substantial comorbidities.